Evolutionary game analysis of emergency medical supply production capacity reserves in nonprofit organizations: A theoretical perspective - Hua Xiao; Guoqiang Luo; Yisheng Wang; Haijun Shuang; Bo Li (PLoS ONE, 2026)
Since the 21st century, global public health emergencies have occurred frequently, posing severe threats to the economic development and social stability of countries worldwide. Against this backdrop, emergency medical supply reserves are particularly crucial—especially the production capacity reserves of non-durable medical materials characterized by high demand, short production cycles, and limited shelf lives. As a theoretical modeling study, this paper adopts the core ideas and analytical methods of evolutionary game theory to construct dynamic evolutionary game models for the cooperative production capacity reserves of emergency medical supplies between nonprofit organizations (NPOs) and reserves enterprises under two scenarios: “perfect competition” and “government incentive policy intervention.” Key factors including reputation benefits, social disaster reduction benefits, and opportunity costs are incorporated to systematically explore the impacts of multiple variables on the decision-making of both cooperative parties. Meanwhile, numerical simulation is employed to quantitatively analyze the operational mechanisms of government incentive policies, specifically one-time subsidies, revenue sharing, cost subsidies, and supervisory penalties. The research findings are as follows: First, the synergistic effect of perfect competition and government incentive policies can promote the evolutionary game system toward cooperative equilibrium. Among these factors, the impact of the incentive allocation coefficient is context-dependent, requiring scientific calibration to balance the interest demands of both parties. Second, the reserves cost-benefit ratio is a core threshold variable determining cooperative behavior. Perfect competition alone tends to fail under high cost-benefit ratios, while the “government-led—NPO-supplemented” collaborative incentive model can break through this threshold constraint via “long-term empowerment + short-term efficiency improvement.” Third, enterprises’ opportunity costs exert a significant negative impact on cooperation, whereas supervisory penalties exceeding a critical threshold can inhibit speculative behaviors and enhance cooperative willingness. Finally, the research findings of this paper are verified through simulation with the background of emergency medical reserves in Chongqing, China. Based on these findings, this study proposes countermeasures including optimizing the incentive allocation mechanism, constructing a collaborative incentive system, and improving the disciplinary constraint mechanism. This research provides new perspectives and practical guidance for optimizing the emergency medical material reserves system and ensuring the stable development of emergency reserves cooperation.